2019
DOI: 10.1002/cey2.19
|View full text |Cite
|
Sign up to set email alerts
|

Carbon materials from melamine sponges for supercapacitors and lithium battery electrode materials: A review

Abstract: With the increasing energy demand together with the deteriorating environment and decreasing fossil fuel resources, the development of highly efficient energy conversion and storage devices is one of the key challenges of both fundamental and applied research in energy technology. Melamine sponges (MS) with low density, high nitrogen content, and high porosity have been used to design and obtain three‐dimensional porous carbon electrode materials. More importantly, they are inexpensive, environment‐friendly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(76 citation statements)
references
References 101 publications
0
76
0
Order By: Relevance
“…Along with the deterioration of environment pollution and intensification of the energy crisis, exploring green and renewable technology for energy storage and conversion is becoming an urgent issue. [1][2][3] Despite great success in commercialization of lithium ion batteries (LIBs), [4][5][6] the high cost and scarcity application in SIBs because of their high theoretical capacity, high redox activity, and lamellar structure similar to graphite. Among these materials, SnS 2 featuring a typical CdI 2 -type crystal structure has been considered as a prospective candidate as anode for SIBs on account of its high specific capacity up to 1137 mAh g −1 , large interlamellar spacing of 0.59 nm, and low operation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the deterioration of environment pollution and intensification of the energy crisis, exploring green and renewable technology for energy storage and conversion is becoming an urgent issue. [1][2][3] Despite great success in commercialization of lithium ion batteries (LIBs), [4][5][6] the high cost and scarcity application in SIBs because of their high theoretical capacity, high redox activity, and lamellar structure similar to graphite. Among these materials, SnS 2 featuring a typical CdI 2 -type crystal structure has been considered as a prospective candidate as anode for SIBs on account of its high specific capacity up to 1137 mAh g −1 , large interlamellar spacing of 0.59 nm, and low operation potential.…”
Section: Introductionmentioning
confidence: 99%
“…The mesopores in NOCSs can provide additional channels for electrolyte ion transport, thereby reducing the ion diffusion resistance. [32] In order to study the capacitive properties of NOCSs, CV and GCD were used to evaluate the electrochemical performance, respectively. Figure 4a reveals the CV grams of NOCS-650, NOCS-750, NOCS-850 and NOCS-950 at the scan rate of 1.0 mV s À 1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[26,31] Compared with other materials, melamine foams have the advantages of light weight, high specific surface area, and abundant pore structure, etc. [32] To satisfy the requirement of electrodes, a carbonization process under inert atmosphere is carried out to improve the conductivity and specific surface area of melamine foam. [33] By direct carbonization, a novel heteroatom-doped carbon body with a low density, high conductivity, and three-dimensional (3D) network could be conveniently prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, sulfur materials are infiltrated to conductive carbon hosts with various morphologies and microstructures. It has been reported that several types of carbon hosts, including hollow carbon, [19] porous carbon, [20] disordered carbon nanotubes, [21] mesoporous carbon nanoparticles, [22] double-shelled hollow carbon spheres, [23] and carbon foam, [24] have made significant enhancement in delivering specific capacity and cycling stability of Li-S batteries. However, the preparation of these complicated carbon materials involves several complicated and energy-intensive steps, [25][26][27] increasing the thermal budget and carbon footprint.…”
Section: Introductionmentioning
confidence: 99%